MENCARI KEPALA DAERAH YANG JUJUR DAN ADIL - SUNARNO - (Universitas Slamet Riyadi, 2010)
AbstractsElection becomes a means of the process of democratization that must be conducted directly, publicly, freely, undisclosely, reliable and fairness. Based on the above norms, especially for the local election, it is hoped that a responsible and potential capable local leader/chief and/or vice local leader/chief will emerge. Yet, there are many disappointed incidents that need to be concerned during and after the election complete, such as the fight between supporters’ candidates, the unfair ballot counting, money politics and other dirty tricks. Those proved that the rules of law are still neglected during the local election. Considering that negligence, it is necessary (a) to recover the article 581 UU Number 32/2004 (b) to compromise between the law assurance, justice and benefits, and (c) to educate people about the culture of law, especially for the culture of personal law to be the open culture of law. Keywords:local leader/chief, reliable.